2022
DOI: 10.21203/rs.3.rs-1961934/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Study of knowledge, attitude and anxiety in Kurdistan-region of Iraqi population during the monkeypox outbreak in 2022: An online cross-sectional study

Abstract: Background On July 23, the WHO declared the rapidly spreading monkeypox (MPX) epidemic as a Public Health Emergency of International Concern (PHEIC). This study attempted to assess the knowledge, attitude, and anxiety levels of the general population during the MPX outbreak. Methods An online cross-sectional survey was conducted during the period July 27 and July 30, 2022, using a convenience sampling method. The questionnaire was adapted and developed after an in-depth review of the previous studies. Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 33 publications
(62 reference statements)
3
9
0
Order By: Relevance
“…Social media was the most comprehensive source of information about mpox, as reported by the study participants. This is consistent with similar studies conducted in eight Middle Eastern countries [ 20 ], as well as in the Kurdistan region of Iraq [ 21 ], Lebanon [ 23 ] and Saudi Arabia [ 4 ]. Additionally, in Czeck, social media was the second-most utilized source of information about human mpox [ 24 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Social media was the most comprehensive source of information about mpox, as reported by the study participants. This is consistent with similar studies conducted in eight Middle Eastern countries [ 20 ], as well as in the Kurdistan region of Iraq [ 21 ], Lebanon [ 23 ] and Saudi Arabia [ 4 ]. Additionally, in Czeck, social media was the second-most utilized source of information about human mpox [ 24 ].…”
Section: Discussionsupporting
confidence: 92%
“…It was noted in previous studies that epidemics and pandemics cause fear in the general population and restrict their activities [ 18 , 19 , 20 ]. Fear and anxiety from mpox spread were reported among the Iraqi population in Kurdistan [ 21 ] and Saudi Arabia [ 22 ]. But, in Saudi Arabia, mpox caused less worry than COVID-19 among the general population [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, 76.7% of the study participants had average knowledge, and only 6.3% had good knowledge regarding Mpox disease, its transmission, prevention, and treatment. The present study results align with previous studies revealing defects in knowledge regarding Mpox disease between Italian physicians, Jordanian and Kuwaiti healthcare workers, the general public in Saudi Arabia, Lebanon and Iraq, and medical students from various countries [ 1 , 23 , 24 , 25 ]. A study from Saudi Arabia reported that the overall knowledge regarding Mpox disease was poor among the general public and more than half of the respondents had low knowledge about Mpox [ 26 ].…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, there was a significant association between attitudes toward Mpox with gender, age groups, academic degree, and discipline. For example, a study from Iraq reported a better knowledge about Mpox disease among males in the general population [ 24 ]. Regarding attitudes, it was reported that attitudes change according to age, level of education, gender, and region of the participants.…”
Section: Discussionmentioning
confidence: 99%